2020
DOI: 10.1186/s40360-020-0401-z
|View full text |Cite
|
Sign up to set email alerts
|

The chemotactic properties of various topical brimonidine tartrate ophthalmic preparations

Abstract: Background: The study aimed to evaluate and compare the leukocyte chemotactic activities of various brimonidine tartrate (BT) eye drop formulations. Methods: A 96-well dot-blot platet using a Boyden-style well was used to study the chemotactic effects of BT ophthalmic preparations. A modification was made to create blind wells where the tested agents were placed. Leukocytes were isolated from the peripheral blood of healthy volunteers. As positive controls, we used diluted drugs, benzalkonium chloride solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although brimonidine has been found to display anti-inflammatory properties in the erythematous skin through the modulation of the vascular barrier function [59], no information is available on its possible anti-inflammatory activity in the diseased eye. Rather, chemotactic properties of various brimonidine formulations in respect to leukocyte migration may determine undesirable inflammatory complications to the eye [60]. Additionally, allergic conjunctivitis and granulomatous uveitis in the elderly can occur after brimonidine administration presumably through activation of T-cells/macrophages [61].…”
Section: Mechanisms Leading To Rgc Protectionmentioning
confidence: 99%
“…Although brimonidine has been found to display anti-inflammatory properties in the erythematous skin through the modulation of the vascular barrier function [59], no information is available on its possible anti-inflammatory activity in the diseased eye. Rather, chemotactic properties of various brimonidine formulations in respect to leukocyte migration may determine undesirable inflammatory complications to the eye [60]. Additionally, allergic conjunctivitis and granulomatous uveitis in the elderly can occur after brimonidine administration presumably through activation of T-cells/macrophages [61].…”
Section: Mechanisms Leading To Rgc Protectionmentioning
confidence: 99%
“…Moreover, miR-186 can act on the target gene YY1 in the treatment of human NSCLC. 26 Hence, we further transfected miR-134-5p-mimics/sh-YY1 and miR-384mimics/sh-YY1 into KATO III to detect the biological function of the cells. It was found that after transfection of sh-YY1,…”
Section: Kato III To Observe the Change In Cell Biological Functionmentioning
confidence: 99%